Uncinia auceps (Cyperaceae): a new endemic hooked sedge for the Chatham Islands - de Lange, P.j. (Phytotaxa, 2013)
Uncinia auceps is described as a new species from Chatham Islands, New Zealand. The new species is segregated from and compared with U. uncinata, a species endemic to the other New Zealand islands. Uncinia auceps occurs mainly in forest habitats on most of the main islands of the Chatham Island archipelago. In addition, a distribution map and the conservation status of the new species are presented.